2020
DOI: 10.1159/000509378
|View full text |Cite
|
Sign up to set email alerts
|

Thin Slices and Maximum Intensity Projection Reconstructions Increase Sensitivity to Hyperdense Middle Cerebral Artery Sign in Acute Ischemic Stroke

Abstract: Introduction: Cranial nonenhanced CT (NECT) imaging in hyperacute ischemic stroke is rarely used for assessing arterial obstruction of middle cerebral artery by identifying hyperdense artery sign (HAS). Considering, however, its growing importance due to its impact on the decision-making process of thrombolysis with or without mechanical thrombectomy improved sensitivity to HAS is necessary, particularly in the group of less experienced clinicians being frequently the first one assessing the presence of HAS on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
(12 reference statements)
1
6
0
Order By: Relevance
“…Using exclusively slices at a thickness of 1 mm in the present study, sensitivity and specificity of two blinded neuroradiologists were 80 and 97%, as well as 93 and 71%, respectively. This is in keeping with results from another study comparing performances of human readers with different slice thicknesses ( 34 ) where sensitivity (73%) and specificity (83%) were best with 1 mm slices and worsened with increasing slices thickness. Comparing AI and human readers, very similar results were presented in 2019 by a group using another commercial application (Nico.lab®) in 59 patients with proven LVO out of 107 ( 29 ).…”
Section: Discussionsupporting
confidence: 88%
“…Using exclusively slices at a thickness of 1 mm in the present study, sensitivity and specificity of two blinded neuroradiologists were 80 and 97%, as well as 93 and 71%, respectively. This is in keeping with results from another study comparing performances of human readers with different slice thicknesses ( 34 ) where sensitivity (73%) and specificity (83%) were best with 1 mm slices and worsened with increasing slices thickness. Comparing AI and human readers, very similar results were presented in 2019 by a group using another commercial application (Nico.lab®) in 59 patients with proven LVO out of 107 ( 29 ).…”
Section: Discussionsupporting
confidence: 88%
“…In addition, the continuity of the blood vessel is lost, resulting in a point-like appearance that is difficult to verify as a thrombus. However, thrombus detection by thin-slice noncontrast CT and MIP is effective [4,7]. Using MIP, blood vessels, which are visualized as dots in a single slice, can be visualized as a single vascular structure when multiple slices are combined.…”
Section: Discussionmentioning
confidence: 99%
“…Two neurosurgeons and one neurologist with expertise in endovascular and cerebral infarction treatment evaluated the results independently. Studies show that MIP without IR is effective in detecting thrombus [4,7]. The aim of this study was not to detect, but to visualize the entire thrombus.…”
Section: Thrombus Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Many attempts have been made to improve the sensitivity of the hyperdense MCA sign [ 8 , 9 , 12 , 13 ]. Previous reports showed that an acute thromboembolus could be detected with higher sensitivity on 1 or 1.5 mm thin-section non-enhanced CT than on 5 mm non-enhanced CT [ 8 , 9 , 13 , 14 ]. However, the increased number of images and the low signal-to-noise ratio have been reported as drawbacks of thin-section images [ 9 ].…”
Section: Introductionmentioning
confidence: 99%